Exogenous ALA promotes tomato fruit quality and pigment metabolism: physiological mechanisms - Chen, Jiaqi; Li, Ruirui; Wang, Junwen; Feng, Junfang; He, Yongmei; Bai, Peng; Shang, Xingpan; Wu, Yue; Yu, Jihua; Tang, Zhongqi; Zhang, Guobin; Xie, Jianming; et al. (Frontiers in Nutrition, 2026)
Fruit pigmentation serves as a critical phenotypic indicator of commercial quality in tomato. The strategic application of exogenous plant growth regulators has emerged as a sustainable approach for quality enhancement. 5-Aminolevulinic acid (ALA), as a natural plant growth regulator, has been demonstrated to promote plant growth and enhance fruit quality. In this study, the impact of ALA on the color and quality changes during tomato (Solanum lycopersicum cv. 184) fruit red ripe was investigated. Fruit at the fruit setting stage was treated with 200 mg·L−1ALA, and the content of intermediate products in chlorophyll and carotenoid synthesis, as well as the activities of related enzymes and gene expression levels, were dynamically monitored. Additionally, color parameters of fruit peel, soluble sugar and organic acid components were determined. Results indicated that ALA significantly upregulated the expression of genes related to chlorophyll degradation (including SlCLH2, SlPPH, and SlSGR). Meanwhile, the expression levels of genes involved in carotenoid synthesis upregulated by exogenous ALA, and the activities of enzymes were also significantly enhanced, including PDS, PSY, and LCYB, which leading to higher levels of lycopene, β-carotene, and other carotenoids accumulated in tomato fruits, thereby improving changes of fruit color. Besides, 200 mg·L−1 ALA treatment significantly increased the content of glucose and fructose in the fruit, while reducing the content of malic acid and citric acid, thus enhancing the sugar-acid ratio of the fruit. In conclusion, treatment with 200 mg·L−1 ALA can effectively promote the carotenoids biosynthesis and accumulation while improving fruit flavor quality.